Pengaruh Inflasi, Suku Bunga (BI Rate), Produk Domestik Bruto (PDB) Terhadap ROA (Studi Pada Bank Pembiayaan Rakyat Syariah (BPRS) di Indonesia Tahun 2009-2016) - Yutisa Tri Cahyani (Institut Agama Islam Negeri Madura, 2018)
Sharia financing banks serve and be source of capital for small and micro business community. After the crisis in 2008, the profitability of the sharia financing banks has decreased significantly. So the impact on slowing economic growth, rising financing stalled and declining market share of Islamic banking. This study used quantitative research methods. Data collection techniques used were documentation and analyzed using multiple regression analysis. With a total population of all sharia financing banks in Indonesia during the eight-year period from 2009 to 2016. The results of this study prove that (1) Inflation does not affect the ROA with a significance value of 0,382 and F arithmetic amounted to 0,788, (2) The interest rate a significant negative affect on ROA with a significance value of 0,029 and F arithmetic amounted to 5,268, (3) GDP does not affect the ROA with a significance value of 0,062 and F calculate equal to 3,774, (4) Inflation, Interest Rate and GDP simultaneously has of effect on ROA with a significance value of 1,66 and F count equal to 1,835.